Thrombocytosis as a predictor of thromboembolic complications in patients with malignant diseases - Jakovljević, Branislava; Maksimović, Siniša; Jakovljević, Aleksandar; Jović, Darko; Latinović, Ljiljana; Ćulum, Jovan; Trkulja, Nebojša; Sibinčić, Sanja; Spahic, Amir (International Journal of Research in Medical Sciences, 2017)
Background: To prove the frequency of thrombocytosis in patients with cancer, and the importance of anticoagulant therapy. Thrombocytosis represents an elevated platelet count of more than 350,000/mm3 which is one of the risk factors for venous thromboembolism. Methods: This study has analyzed 146 patients who were hospitalized at the Oncology Clinic of the University Clinical Centre, Banja Luka and the Day Oncology Hospital “S.tetik”, Banja Luka in the period between 2009 and 2014. These were patients with breast tumor, gastrointestinal or gynecological malignancies. Thrombocytosis was detected in 38 patients in the moment of diagnosing. All examinees were analyzed by sex, age, primary site of tumor, presence of comorbidity, relevant laboratory analyses, clinical stage of the disease (metastatic or localized disease). Results: In the observed sample of 146 patients, thrombocytosis was detected in 38 patients in the moment of diagnosing the disease (26%). Through the follow-up, DVT (deep venous thrombosis) was found in 13 patients (34.2%) and anticoagulant therapy was administered. Out of patients who were not on anticoagulant therapy because they had no thrombotic manifestations (25 patients, 65.8%), 2 ended up experiencing the development of a clinical presentation of massive pulmonary embolism with fatal outcome. Conclusions: The occurrence of thromboembolism significantly increases morbidity and mortality, as well as the total cost of treating cancer patients. Regardless of the fact that cancer patients are at a high risk of thromboembolic events, thromboembolic prophylaxis has not been adopted as a standard therapeutic modality because of potential bleeding.